Identifikasi Drug Related Problems (DRPs) Pada Pasien Penyakit Ginjal Kronis di Instalasi Rawat Inap Rumah Sakit X Surakarta Tahun 2024 - Mubarok, Afrizal; Fortuna, Tista Ayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Chronic kidney disease (CKD) is a condition characterized by impaired kidney function lasting at least three months. In patients with chronic kidney failure, the use of multiple medications has the potential to increase the risk of drug-related problems (DRPs), which can hinder the expected effectiveness of therapy. Objective: This study aims to determine the incidence of DRPs in patients with chronic kidney disease treated at the inpatient facility of Hospital X in Surakarta. Methods: This study employed a cross-sectional methodology and a non-experimental design. Data were collected retrospectively through the medical records of patients with chronic kidney disease treated at the inpatient facility of Hospital X in Surakarta. Data analysis was performed univariately by describing and analyzing the study variables. DRPs were identified based on the Pharmaceutical Care Network Europe (PCNE) classification. Results: The most common comorbidity was anemia at 27.93%, while the most frequently used drug class was vitamins and minerals at 24.70%. Of the 108 patients analyzed, 12 patients experienced at least one DRP (11.11%). In total, 15 cases of DRPs were identified with code P1.3 (problem) and codes C3.1, C3.2, C3.3, and C3.4 (causes) from those 12 patients. Conclusion: This study shows the occurrence of DRPs in patients with chronic kidney disease treated at Hospital X in Surakarta.